Environmental regulation and innovation - MIN, Soyeon (KDI School, 2021)
This paper investigates the impact of K-REACH and CCA on innovation, based on the “weak” version of the Porter Hypothesis (PH), using both panels of manufacturing industries and firms in South Korea during 2011-2018. In 2015, South Korea newly enforced two stringent chemical regulations, the K-REACH and CCA to protect public health and the environment from chemical disasters. Given there are only very few relevant studies, our analysis will be the first attempt to examine the PH that a well-crafted environmental policy induces innovation activities of firms. Our empirical results are based on sequential adoption of the quasi-experimental method of Propensity Score Matching (PSM) and the Difference in Differences (DID) estimation as well as a standard panel regression. With the innovation activities being measured by R&D expenditure, the number of patent applications, entry rate of new firms and exit rate of existing firms, we find no evidence to support the PH.
Thesis(Master) -- KDI School: Master of Public Policy, 2021
Keywords: Environmental policy--Korea (South); Environmental law--Korea (South)